Effect of recruitment manoeuvres under lung ultrasound-guidance and positive end-expiratory pressure on postoperative atelectasis and hypoxemia in major open upper abdominal surgery: A randomized controlled trial. Issue 2 (February 2023) - Liu, Tao; Huang, Jiapeng; Wang, Xinqiang; Tu, Jiahui; Wang, Yahong; Xie, Chen
Abstract: Background: Postoperative pulmonary complications (PPCs) especially atelectasis and hypoxemia are common during abdominal surgery. Studies on the effect of either recruitment manoeuvres (RMs) or positive end-expiratory pressure (PEEP) on PPCs are controversial. The objective of this study is to evaluate the effect of perioperative lung ultrasound (LUS)-guided RMs combined with PEEP on the reduction of postoperative atelectasis and hypoxemia in major open upper abdominal surgery. Methods: In this randomized controlled trial, 122 adult patients undergoing major open upper abdominal surgery were allocated into three groups: control (C) group (n = 42); PEEP (P) group (n = 40); RMs combined with PEEP (RP) group (n = 40). All patients were scheduled for general anaesthesia using the lung-protective ventilation (LPV) strategy. The levels of PEEP in the three groups were 0 cmH2 O, 5 cmH2 O and 5 cmH2 O. LUS examination was carried out at 3 predetermined time points in each group: 5 min after intubation (T1 ), at the end of surgery (T2 ) and 15 min after extubation (T3 ). Patients with atelectasis on the sonogram in the RP group received LUS-guided RMs at point T2 . LUS scores were used to estimate the severity of aeration loss. The P/F ratio (PaO2 /FiO2 ) at 15min after extubation was used to assess the incidence of postoperative hypoxemia. Primary outcomes were the incidences of postoperative atelectasis and hypoxemia (PaO2 /FiO2  < 300 mmHg). The secondary outcome was the distribution of LUS scores in each lung area. Results: From July 2021 to December 2021, 122 consecutive patients were enrolled. No typical atelectasis was observed 5 min after intubation. The incidence of atelectasis was 52.4%, 50.0% and 42.5% in the C group, P group and RP group at the end of surgery, respectively. The rate of atelectasis in the C group, P group and RP group (after RMs) was 52.4%, 50.0% and 17.5%, respectively, 15 min after extubation ( P  < 0.01). The frequency of postoperative hypoxemia was 27.5%, 15.0% and 5.0% in the C group, P group and RP group, respectively ( P  < 0.017). The increased LUS scores mainly occurred in the superoposterior and inferoposterior quadrants at the end of surgery. Only in the RP group demonstrated a decreased LUS score in the posteriorquadrants after extubation. Conclusions: In patients undergoing major open upper abdominal surgery, an intraoperative mechanical ventilation strategy without PEEP or with PEEP alone did not reduce PPCs. However, PEEP of 5 cmH2 O combined with LUS-guided RMs proved feasible and beneficial to decrease the occurrence of postoperative atelectasis and hypoxemia in major open upper abdominal surgeries.